2014
DOI: 10.12968/bjon.2014.23.7.382
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapy: professional compliance with national guidelines

Abstract: One of the major causes of critical illness in the UK is the deterioration of respiratory function British Thoracic Society (BTS, 2008) Key Points• National evidence based guidelines produced by the British Thoracic Society and local policies exist to support good practice with regard to the prescription and administration of supplementary oxygen. Lack of adherence to these guidelines and policies can contribute to poor patient outcomes and ultimately death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Oxygen therapy is essential in the treatment of patients with respiratory failure. However, studies have observed poor compliance of health professionals with international guidelines concerning the use of oxygen therapy in the acute setting [5]. Potential risks associated with the available oxygen delivery systems are hypoxemia or hyperoxia-induced hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen therapy is essential in the treatment of patients with respiratory failure. However, studies have observed poor compliance of health professionals with international guidelines concerning the use of oxygen therapy in the acute setting [5]. Potential risks associated with the available oxygen delivery systems are hypoxemia or hyperoxia-induced hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid these complications, current guidelines suggest monitoring of oxygen delivery to target oxygen saturation (SpO 2 ) of 88–92% for hypercapnic patients and 94–98% for normocapnic subjects with acute respiratory failure [1, 2]. However, available constant flow devices do not have the ability to titrate oxygen flow according to patients corresponding SpO 2 , while studies have shown poor compliance of health professional with international guidelines [5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive literature about the adverse events of inadequate use of oxygen, this therapy is still poorly prescribed and junior doctors poorly understand the effects and dangers of oxygen [18][19][20]. Changing clinical practice in response to research data (knowledge translation or implementation) is difficult in many areas of medicine, resulting in excess morbidity and mortality and significant additional financial costs [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the move toward comprehensively prescribing oxygen should provide a simple framework to guide staff caring for the patient. Perhaps paramount, however, is the education of health care professionals, particularly the doctors, nurses, and paramedics who are responsible for administering oxygen therapy to patients with COPD 95. Hospitals should institute local policies to improve education and practice, and these should be subject to rigorous audit and reevaluation 55…”
Section: Current Practice and Strategies For Changing Behaviormentioning
confidence: 99%